2015
DOI: 10.1111/ajt.13269
|View full text |Cite
|
Sign up to set email alerts
|

Islet Amyloid in Whole Pancreas Transplants for Type 1 Diabetes Mellitus (DM): Possible Role of Type 2 DM for Graft Failure

Abstract: Long‐term results with whole pancreas (WPTx) and islet transplantation (IT) continue to be suboptimal. Graft failure with undetectable C‐peptide level is attributed to graft sclerosis (chronic rejection), recurrence of Type 1 diabetes mellitus (DM), or insufficient islet mass. In contrast, graft failure with measurable C‐peptide has overlapping clinical features with Type 2 DM (suggesting persistent but insufficient β cell function), but is poorly understood. In general, the morphological substrate for islet f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Westermark et al reported varying degrees of amyloid severity in 33-44% of engrafted islets in three out of four T1D recipients of clinical islet transplants ; intriguingly, the patient in which no amyloid was observed had the lowest glycated hemoglobin levels of the four patients in this study. Islet amyloid was also reported to be present in most islets in two T1D recipients of whole pancreas allografts presenting with graft failure (Leõn Fradejas et al 2015), suggesting that amyloid may also contribute to failure of pancreas transplants. Clear demonstration of a causal role R68 H C Denroche and C B Verchere IAPP and type 1 diabetes 60 2 :…”
Section: Iapp Aggregation and Islet Transplant Dysfunctionmentioning
confidence: 95%
See 2 more Smart Citations
“…Westermark et al reported varying degrees of amyloid severity in 33-44% of engrafted islets in three out of four T1D recipients of clinical islet transplants ; intriguingly, the patient in which no amyloid was observed had the lowest glycated hemoglobin levels of the four patients in this study. Islet amyloid was also reported to be present in most islets in two T1D recipients of whole pancreas allografts presenting with graft failure (Leõn Fradejas et al 2015), suggesting that amyloid may also contribute to failure of pancreas transplants. Clear demonstration of a causal role R68 H C Denroche and C B Verchere IAPP and type 1 diabetes 60 2 :…”
Section: Iapp Aggregation and Islet Transplant Dysfunctionmentioning
confidence: 95%
“…Islet amyloid has been found in human islets transplanted into diabetic immune-deficient mice (Westermark et al 1995, 1999, Finzi et al 2005, Bohman & Westermark 2012, Potter et al 2015; hIAPP transgenic mouse islets transplanted into syngeneic or immunedeficient diabetic mice (Udayasankar et al 2009, Westwell-Roper et al 2011, and non-human primate islet allografts (Liu et al 2012). In addition, biopsies of whole pancreas transplants and liver-engrafted islets obtained at autopsy from T1D subjects have demonstrated varying degrees of islet amyloid formation , Leõn Fradejas et al 2015. Despite being absent at the time of transplantation, islet amyloid forms rapidly in hIAPP transgenic mouse islets and human islets engrafted in diabetic mouse recipients, and its severity progresses over time (Westermark et al 2003, Udayasankar et al 2009).…”
Section: Iapp Aggregation and Islet Transplant Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other programs have attempted a more scientific definition; such as reporting a pancreatic graft as failed if there is loss of insulin independence, or when the pancreas graft has been removed or the patient has died . Other factors, such as C‐peptide levels, hemoglobin A1C (HbA1C) levels, or dose and duration of insulin therapy are used by some programs to determine when graft failure has occurred (personal communication with committee members). As the OPTN uses statistical models based on center‐reported and center‐determined pancreas graft failure to assess pancreas program performance, differences in reporting may influence whether a pancreas program will be identified for poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main points of discussion was whether a defined C‐peptide level could serve as a threshold to define pancreas graft failure. Because the literature on C‐peptide levels as a marker of graft failure was sparse and inconclusive, and because C‐peptide data are not routinely reported to the OPTN, the Pancreas Outcomes Subcommittee decided to perform their own multicenter retrospective C‐peptide data collection study. The goal of this data collection was to determine whether a defined C‐peptide level could serve as a threshold level to define pancreas graft failure as reported to the OPTN.…”
Section: Introductionmentioning
confidence: 99%